Educational services and school dropout rates: an analysis of alternative basic education Nueva Cajamarca, Peru - Minga Sarmiento, Milder (2025)
Objective: To determine the relationship between educational service and school dropout at the “Manuel Fidencio Hidalgo Flores” Alternative Basic Education Center (CEBA, by its Spanish acronym), in the district of Nueva Cajamarca, Peru, in 2024. Methods: A quantitative study based on basic research, with a correlational and cross-sectional design. The population consisted of 300 students from the institution, and the sample included 166 students selected through simple probabilistic sampling, spanning the initial, intermediate, and advanced levels. A Likert-scale questionnaire was used for data collection, and Spearman’s rank correlation coefficient was employed for inferential analysis. Results: The levels of the “educational service” variable were: low (2.41%), good (33.73%), and high (63.86%), while the levels of the “school dropout” variable were: low (6.63%), medium (87.95%), and high (5.42%). These results indicate general acceptance of educational services, although improvements in teaching quality are needed. The relationship between “educational service” and “school dropout” was negative, very weak, and statistically significant (rho = -0.192, p = 0.013 < 0.05). Conclusions: There is a significant relationship between educational service and school dropout at the “Manuel Fidencio Hidalgo Flores” CEBA. Moreover, the “pedagogy” dimension was identified as one of the contributing factors to school dropout.